2017
DOI: 10.1021/acs.jmedchem.7b00231
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Clinical Candidate 1-{[(2S,3S,4S)-3-Ethyl-4-fluoro-5-oxopyrrolidin-2-yl]methoxy}-7-methoxyisoquinoline-6-carboxamide (PF-06650833), a Potent, Selective Inhibitor of Interleukin-1 Receptor Associated Kinase 4 (IRAK4), by Fragment-Based Drug Design

Abstract: Through fragment-based drug design focused on engaging the active site of IRAK4 and leveraging three-dimensional topology in a ligand-efficient manner, a micromolar hit identified from a screen of a Pfizer fragment library was optimized to afford IRAK4 inhibitors with nanomolar potency in cellular assays. The medicinal chemistry effort featured the judicious placement of lipophilicity, informed by co-crystal structures with IRAK4 and optimization of ADME properties to deliver clinical candidate PF-06650833 (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(135 citation statements)
references
References 64 publications
4
131
0
Order By: Relevance
“…In a previous publication (7), we reported that IL-1-induced cytokines were minimally impacted by an IRAK4 inhibitor at a concentration of 10 M. However, the inhibitor used in that study had poor physical properties and did not allow us to completely test its pharmacology. The inhibitor PF-06650833 has superior cell potency, is highly selective for IRAK4, and maximally covers IRAK4 at a concentration of 200 nM with no inhibition of other kinases, including IRAK1 (18). Therefore, the data presented in this study substantiate our previous finding of partial inhibition of IL-1-mediated cytokine by an IRAK4 kinase inhibitor.…”
Section: Inhibition Of Irak4 In Primary Human Dermal Fibroblasts Usinsupporting
confidence: 87%
See 1 more Smart Citation
“…In a previous publication (7), we reported that IL-1-induced cytokines were minimally impacted by an IRAK4 inhibitor at a concentration of 10 M. However, the inhibitor used in that study had poor physical properties and did not allow us to completely test its pharmacology. The inhibitor PF-06650833 has superior cell potency, is highly selective for IRAK4, and maximally covers IRAK4 at a concentration of 200 nM with no inhibition of other kinases, including IRAK1 (18). Therefore, the data presented in this study substantiate our previous finding of partial inhibition of IL-1-mediated cytokine by an IRAK4 kinase inhibitor.…”
Section: Inhibition Of Irak4 In Primary Human Dermal Fibroblasts Usinsupporting
confidence: 87%
“…To confirm that the observations in the heterologous expression system are relevant to primary cells and not due to artifacts of overexpression of the constructs, we treated primary human neonatal dermal fibroblasts with 2 ng/ml IL-1␤ and monitored phosphoprotein signaling and cytokine release in the presence of the highly selective and potent IRAK4 inhibitor PF-06650833 (compound 40 in Lee et al (18)). A concentration of 200 nM PF-06650833, which completely suppresses IRAK4 autophosphorylation (see Fig.…”
Section: Inhibition Of Irak4 In Primary Human Dermal Fibroblasts Usinmentioning
confidence: 96%
“…To translate our findings, we tested 2 different IRAK4 inhibitors. Of these, PF06650833 is being tested in clinical trial (35), and AS2444697 was shown to protect inflammation-associated renal failure in rats (36). We previously showed that AS2444697 blocks IL-1β-induced NF-κB activation in pancreatic cancer cells (27,36).…”
Section: Resultsmentioning
confidence: 99%
“…Innate immune signaling has an essential role in inflammation, and the dysregulation of signaling components of this pathway is increasingly being recognized as an important factor in cancer initiation, progression, and metastasis, as well as in autoimmunity. However, among the four IRAKs, only the IRAK4 kinase domain structure has been determined, both alone and in complex with various inhibitors (10,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). No structural information is currently available for IRAK1.…”
Section: Significancementioning
confidence: 99%